2005
DOI: 10.1111/j.1365-2990.2005.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3 dioxygenase and quinolinic acid Immunoreactivity in Alzheimer's disease hippocampus

Abstract: The present immunohistochemical study provides evidence that the kynurenine pathway is up-regulated in Alzheimer's disease (AD) brain, leading to increases in the excitotoxin quinolinic acid (QUIN). We show that the regulatory enzyme of the pathway leading to QUIN synthesis, indoleamine 2,3 dioxygenase (IDO) is abundant in AD compared with controls. In AD hippocampus, both IDO- and QUIN-immunoreactivity (-IR) was detected in cortical microglia, astrocytes and neurones, with microglial and astrocytic expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
251
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 296 publications
(266 citation statements)
references
References 24 publications
11
251
1
1
Order By: Relevance
“…Although the factors determining the level of expression of kynurenine pathway enzymes in the intact brain remain to be clarified, the present work clearly indicates that a diverse range of neuronal types have the potential to produce these enzymes in the human brain. We previously showed that only a very low level of QUIN immunoreactivity is found in temporal neocortical and hippocampal areas in control brain tissue (Guillemin et al, 2005c) and that concentrations of QUIN in normal cerebral tissue are extremely low (Ͻ1 nM) (Guillemin et al, 2007). The present data are entirely consistent with our previous observations.…”
Section: Expression Of Kynurenine Pathway Enzymes In Human Fetal Neursupporting
confidence: 83%
See 1 more Smart Citation
“…Although the factors determining the level of expression of kynurenine pathway enzymes in the intact brain remain to be clarified, the present work clearly indicates that a diverse range of neuronal types have the potential to produce these enzymes in the human brain. We previously showed that only a very low level of QUIN immunoreactivity is found in temporal neocortical and hippocampal areas in control brain tissue (Guillemin et al, 2005c) and that concentrations of QUIN in normal cerebral tissue are extremely low (Ͻ1 nM) (Guillemin et al, 2007). The present data are entirely consistent with our previous observations.…”
Section: Expression Of Kynurenine Pathway Enzymes In Human Fetal Neursupporting
confidence: 83%
“…For this study, autopsy tissue was sampled from two neurologically normal male patients (39 and 64 years old), both with cardiac arrest as cause of death. Series of 45 m cryosections were processed for immunohistochemistry using the avidin-biotin complex detection system as described previously (Guillemin et al, 2005c). Freefloating sections were washed in 50% ethanol for 3 ϫ 15 min at 37°C and then incubated in 3% H 2 O 2 for 20 min to quench endogenous peroxidase activity.…”
Section: Methodsmentioning
confidence: 99%
“…Besides that, it is also reported that excessively expressed IDO could lead to depression following ischemic stroke (10,11). Moreover, over-expressed IDO in hippocampus may also play a role as a pathological factor in Alzheimer disease (12). In the paper our team published in 2012, it has already been shown that NBP also exerts the therapeutic effect in vascular dementia (3), which may be partially explained by previously reported functions of IDO.…”
Section: A Series Of Nbp Potential Targets Resulting From Search Are mentioning
confidence: 49%
“…Regarding AD pathomechanism post mortem immunocytochemistry in the hippocampus of AD patients revealed elevated TDO2 levels [21] and amyloid-β treatment increased TDO2 expression [22]. Thus, elevated TDO2 level in one year old rats might anticipate pathological changes.…”
Section: Discussionmentioning
confidence: 95%